A content analysis of TikTok videos and its role in propagating (mis)information about COVID-19 and the ongoing distribution of vaccines. - Francis, Courtnee (The IIE, 2022)
The popularity of social media amongst the youth has resulted in an influx of misinformation spread regarding important topics. With the onset of COVID-19, the misinformation was quick to circulate, and as it grew into a global concern with initiating lockdowns, many actively sought after easily digestible sources, most often social media. However, wrought with ill-informed content creators, the youth were most vulnerable to the inaccurate information, which has created many critics for the virus and vaccines. Through content analysis, the most common topics and the narrative connected to them were identified to discover patterns in theCOVID-19 TikTok content consumed by the youth and whether this is pro or anti contexts. The most discussed themes were mask related, indicating that most people's frustrations lie with the mandatory mask-wearing which ignites feelings of restriction. This implies that the youth are consuming content that is placing the demographic at risk as masks have been found to be one of the most popular ways to prevent contracting COVID-19 – especially when the positive numbers amongst the youth are increasing. Through the study, it was identified that the most popular content was factual, informative and accurate – leaving a positive impression on the viewer of their responsibility to make their community safer.
Keywords: Social media; Propaganda; Disinformation; Health